Accelerated Fibrinolysis: A Tendency to Bleed? - Mehic, Dino; Pabinger, Ingrid; Gebhart, Johanna (Hämostaseologie, 2025)
Hyperfibrinolysis is rarely investigated as an underlying mechanism in patients with mild-to-moderate bleeding disorders (MBDs) and bleeding disorders of unknown cause (BDUC). Hereditary hyperfibrinolytic disorders, including α2-antiplasmin (α2-AP) deficiency, plasminogen activator inhibitor type 1 (PAI-1) deficiency, Quebec platelet disorder, and tissue plasminogen activator (tPA) excess, present with mild-to-moderate bleeding symptoms that are common in patients with MBD or BDUC, but may also manifest as life-threatening bleeding. This review summarizes the available data on hyperfibrinolysis in MBD and BDUC patients, and its assessment by various methods such as measurement of fibrinolytic factors, global hemostatic assays (e.g., viscoelastic testing, turbidity-based plasma clot lysis), and fluorogenic plasmin generation (PG). However, evidence on the relationship between hyperfibrinolytic profiles and bleeding severity is inconsistent, and, although found in some coagulation factor deficiencies, has not been universally observed. In BDUC, increased tPA activity and paradoxical increases in thrombin-activatable fibrinolysis inhibitor and α2-AP have been reported. Some studies reported no change in PAI-1 levels, while others observed reduced PAI-1 levels in a significant subset of patients. The tPA-ROTEM (tPA-rotational thromboelastometry) assay identified a hyperfibrinolytic profile in up to 20% of BDUC patients. PG analysis revealed a paradoxically reduced peak plasmin, but showed strong predictive power in differentiating BDUC patients from healthy controls. Although global fibrinolytic assays may help identify hyperfibrinolytic profiles as a potential cause of increased bleeding in some MBD or BDUC patients, the utility of measuring fibrinolytic factors requires further investigation. Tranexamic acid is commonly used to treat hereditary hyperfibrinolysis and is also recommended in MBD/BDUC patients prior to hemostatic challenges.
Keywords: fibrinolytic disorders; fibrinogen/fibrin; plasminogen activator inhibitor; coagulation factor; von Willebrand disease